Supply Chain Management of Ginger Coffee at UD Bintang Surayyah, Palu : A Qualitative Case Study - Zulfadli R. Lakadjo; Fatlina Zainuddin; Syamsuddin; Suryadi Hadi (LP2M IAIN Palopo, 2026)
purpose: This study aims to examine the ginger coffee supply chain management at UD Bintang Surayyah, identify the main challenges, and develop appropriate strategies to improve the effectiveness of sustainable supply chain management. Methods: This study is a qualitative study using a descriptive approach with observation, interviews, and documentation as research methods. The informants in this study were selected through purposive sampling and consisted of business owners, farmers, and retailers; their responses were then analyzed using triangulation.. Results: The research findings show that the ginger supply chain at UD Bintang Surayyah consists of upstream, internal, and downstream segments involving farmers, production facilities, retailers, and consumers. The main challenges identified include inconsistent quality of ginger raw materials, high prices for ginger raw materials due to competition for supply from other businesses, a weak inventory control system, and high distribution costs and lead times. Building stronger partnerships with farmers through formal cooperation agreements, implementing a more structured system for demand forecasting and inventory control, and optimizing the distribution system are expected to be strategies that improve operational efficiency and support business sustainability. Implications: The study is expected to provide practical implications for MSME operators in improving operational efficiency and business sustainability through better supply chain management.